Pengaruh Teknologi Informasi terhadap Pola Komunikasi Generasi Z di Kota Medan, Sumatera Utara - Najahaura Rahma; Ridho Albar Siregar; Zaidah Nur Salamah Lubis; Abdul Malik; Adelyna Oktavia Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology has brought fundamental changes in the communication patterns of generation Z, especially in the city of Medan, North Sumatra. This generation is known as digital natives who are highly dependent on technological devices and the internet in their daily communication. Various digital platforms such as social media, instant messaging applications, and online forums are their main means of establishing social interactions. This study aims to analyze the influence of information technology on the communication patterns of generation Z in the city of Medan, by highlighting aspects of changes in communication style, effectiveness of message delivery, and the social impact of the use of information technology in their lives. The method used in this study is a quantitative method with data collection techniques through Google Form (GForm). The questionnaire was distributed online to respondents who were generation Z domiciled in the city of Medan. The data collected was then analyzed to see the patterns of information technology use in their communication, preferences for the digital platforms used, and the positive and negative impacts they felt. The results showed that the majority of respondents preferred text-based and multimedia communication compared to direct communication, for reasons of convenience, time efficiency, and flexibility in communicating. The findings of this study indicate that although information technology has made communication easier, there are also challenges that arise, such as reduced face-to-face communication capabilities and increased risk of miscommunication due to different interpretations of messages. Therefore, a balance is needed in the use of information technology so that generation Z can maintain effective communication quality, both in the digital world and direct social interactions. By understanding communication patterns, society and policy makers can be wiser in designing digital literacy strategies that support healthier and more productive communication.